2010
DOI: 10.4141/cjss09016
|View full text |Cite
|
Sign up to set email alerts
|

Nitrous oxide fluxes related to soil freeze and thaw periods identified using heat pulse probes

Abstract: . 2010. Nitrous oxide fluxes related to soil freeze and thaw periods identified using heat pulse probes. Can. J. Soil Sci. 90: 409Á418. Surface N 2 O fluxes have not been unequivocally linked to soil profile conditions, in particular the timing of water phase change. The heated needle probe is a sensor that has the potential to monitor in situ apparent volumetric heat capacity (C a ), which considers latent heat transfer, during freezing and thawing. The objective of this study was to relate the timing of N 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…3c), causing greater accumulation of N 2 O s and hence greater emissions during thaw. These model findings were consistent with field observations by Congreves et al (2017) and Wagner-Riddle et al (2010) that overwinter N 2 O emissions increased with greater freezing under conventional tillage vs. no tillage, particularly with surface residue removal. Model findings were also consistent with observations by Teepe et al (2004) that N 2 O emissions during soil thawing rose sharply with increased duration of soil freezing.…”
Section: Ni Effects On Barley Silage Yieldssupporting
confidence: 89%
“…3c), causing greater accumulation of N 2 O s and hence greater emissions during thaw. These model findings were consistent with field observations by Congreves et al (2017) and Wagner-Riddle et al (2010) that overwinter N 2 O emissions increased with greater freezing under conventional tillage vs. no tillage, particularly with surface residue removal. Model findings were also consistent with observations by Teepe et al (2004) that N 2 O emissions during soil thawing rose sharply with increased duration of soil freezing.…”
Section: Ni Effects On Barley Silage Yieldssupporting
confidence: 89%
“…It is not possible to define the exact conditions triggering the N 2 O emission rates in our study, given the limited number of sampling dates. However, other authors have reported that N 2 O emissions in winter occurred due to a temperature increase and subsequent soil thawing and influx of water from melted snow [50] and immediately after water phase change from ice to liquid water after FTEs [60].…”
Section: Gaseous Emissions During Wintermentioning
confidence: 98%
“…Kaiser and Ruser (2000) calculated a mean contribution of 50% of the winter fluxes to the annual N 2 O emission in various regions of Germany with distinctive frost/thaw cycles. Although the processes of enhanced N 2 O release during thawing are not completely clarified, most of the experiments reveal denitrification as the main N 2 O source ( Wagner‐Riddle et al, 2010). In addition to the thaw induced N 2 O pulses, increased flux rates have also been reported under relatively mild conditions in early winter and attributed to the turn‐over of N‐rich crop residues from cauliflowers even at low soil temperatures ( Pfab et al, 2011).…”
Section: N2o Reduction Potential Of Nismentioning
confidence: 99%